Multi-Layered Dynamic Encryption Security Scheme for Cloud Data Storage - Rodriguez, Stephen; Centonze, Paolina (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2017)
This journal article discusses our Dynamic Encryption Key Security Scheme (DEKSS) and the purpose it serves in providing a new security architecture for protecting databases used in technology stacks involving Mobile and Cloud based devices. Our security scheme is a novel architectural strategy that implements a full-stack architecture for the dispatching and management of data between several Cloud Service Providers (CSP) and any number of mobile devices. This strategy can promise data security needs for both mobile devices and cloud service providers without impacting the security requirements of the other party. While there are limitations in being truly secure, such as those recognized by WhiteHat security in their annual report[1], we believe that our security scheme can effectively circumvent potential threats and secure data through folding data using any number of encryption layers for every table and column of data to be stored. Through this approach, we have found our work to be applicable to a variety of different audiences within the cloud security space.